Technology for harmonization of sociopsychophysiological climate in the family based on knowledge about biosocial culture of personality - Kuzmina, K.I.; Somyk, T.M.; Andon, A.P. (Інститут програмних систем НАН України, 2024)
We propose the computer-based technology of harmonization of SPF climate in a family as a quality index of interpersonality relations. The basis for this estimation is biosocial culture of individual, namely, the knowledge about person structure, his functional state and individual adaptive information space (IAIS). The technology includes the series of express diagnostic tests with computer-based interpretation and may be used to optimization of collectives of different level.Prombles in programming 2024; 2-3: 392-399